Bioethics: a comparative study of its concepts, issues and approaches, 2nd ed. - Hashi, Abdurezak Abdulahi (IIUM Press, International Islamic University Malaysia, 2018)
Bioethics is an important and rapidly growing subject of our time. Since the early writings of bioethics in 1920s, when the word bioethics was coined by Fritz Jahr, who described it as an “imperative” field,1 as well as the writings of American biologists, Van Rensseler Potter, who in the early 1970s highlighted further the importance of bioethics,2 the academic works that are set to address foundations and principles of this field had increased in number and volume. For it seeks to establish equilibrium between the needs of advancing modern breakthroughs in the field of biomedicine and the requirements of ethic, scholars in this field highlighted bioethics as a “bridge to the future”, as well as a “science of survival”. This is so because, bioethics functions as an intersection of biology, ecology, medicine and moral values, and addresses moral issues of scientific researches and practices in the fields of biomedicine and biotechnology. With the observable advances in the application of technology in biology and life sciences, there are genuine concerns about the relationship between life sciences, technology, medicine, law, moral values and philosophy. The bottom line of bioethics is the endeavour of ensuring to develop morally guided biosciences; wherein scientific discovers in this area are advanced into greater height, without risking the sanctity of life, now and the future. This work, Bioethics: A Comparative Study of Its Concepts, Issues and Approaches, uses the comparative method and addresses foundations, history, scope, codes, issues and approaches of bioethics. It attempts to address this field in a comparative manner, with an observable emphasis on the Islamic ethical and jurisprudential views on given bioethical issues and practices. The 1st edition of this book was published in 2015, which since then received an encouraging demand for its copies from students, researchers of biosciences and healthcare providers, as well as related readers from the public. IIUM bookshop and IIUM press informed me that copies of the 1st edition of this book have been sold out, and the book is now out of stock, with some demands for its copies. Taking this as an encouraging feedback, the author feels honored to share the updated 2nd edition of the book with its readers. My gratitude and appreciations are, above all, due to Allah (s. w. t.), for His grace and guidance in all times, particularly during the course of this humble work. I also wish to express my appreciation and thanks to those, students, researchers, healthcare providers and lecturers, whose comments and discussions have enriched the subject matters of this book. My heartfelt appreciations are also extended to IIUM Press and Research Management Center of the International Islamic University Malaysia, for sponsoring the publication of this work again. Indeed, without their support and encouragement, the publication of this work would have probably never been achieved. May Allah (s. w. t.), reward them all, and accept our good deeds.